Biofilm detection of clinical isolates of Klebsiella pneumoniae from Pontianak, West Kalimantan - Anggie, Joycely; Fajar Liana, Delima; Mardhia, Mardhia; Mahyarudin, Mahyarudin; Agustina, Risa (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Klebsiella pneumoniae (K. pneumoniae) belongs to the Enterobacteriaceae family, which is known as Gram-negative, encapsulated, and non-motile bacteria. One of its most important virulence factors of K. pneumoniae is the ability to form biofilms. A high percentage of K. pneumoniae as biofilm formation is associated with a high incidence of antibiotic resistance, leading to higher morbidity and mortality. This study aimed to evaluate biofilm formation of clinical isolates of K. pneumonia from Pontianak, West Kalimantan. A total of 24 K. pneumoniae clinical isolates from various specimens were subjected to biofilm formation detection. The biofilm formation was detected by crystal violet formation at wavelength of 570 nm as indicator using microtiter plate assay. As control of biofilm formation was Staphylococcus aureus ATCC 25923, and as control of non-biofilm formation was Staphylococcus epidermidis ATCC 12228. Data on biofilm formation of the isolates from various specimens were analyzed using Fisher’s exact test with SPSS Ver. 26. All the K. pneumoniae clinical isolates were biofilm producer consisting of 19 isolates were strong biofilm producer, four were moderate biofilm producer, and one isolates was weak biofilm producer. No association between biofilm formation and specimen type was observed (p=0.541). In conclusion, all K. pneumoniae clinical isolates from Pontianak, West Kalimantan are identified as biofilm producer.